Project Based Digital Storytelling as a Learning Approach in Developing Copywriting Skills of Indonesian Language Education Students - Renita Br Saragih; Tigor Sitohang; Pontas Jamaludin Sitorus; Hotmaida Lumbangaol (Tabasa: Jurnal Bahasa, Sastra Indonesia, dan Pengajarannya, 2026)
The rapid advancement of digital technology requires copywriting instruction to develop not only persuasive writing skills but also multimodal communication and digital literacy. However, copywriting courses in Indonesian Language Education programs remain largely teacher-centered, limiting students' opportunities to engage in authentic digital learning. This study aimed to examine the effectiveness of Project-Based Digital Storytelling (PBDS) in improving university students' copywriting skills. A quasi-experimental study employing a nonequivalent control group design was conducted with 45 undergraduate students, comprising an experimental group (n = 23) and a control group (n = 22). Data were collected using pretest–posttest copywriting achievement tests and analyzed through descriptive statistics, independent- and paired-samples t-tests, normalized gain (N-Gain), and Cohen's d. The findings revealed that the experimental group significantly outperformed the control group in posttest achievement (p < .001), obtained a higher N-Gain (0.71), and demonstrated a large effect size (d = 1.61). Students also showed marked improvement in multimedia integration, creativity, persuasive message quality, and presentation performance. These findings imply that PBDS is an effective pedagogical approach for integrating persuasive writing, digital storytelling, and multimodal communication while strengthening students' digital literacy and twenty-first-century communication competencies in higher education.   Perkembangan pesat teknologi digital menuntut agar pengajaran penulisan iklan tidak hanya mengembangkan keterampilan menulis yang persuasif, tetapi juga komunikasi multimodal dan literasi digital. Namun, mata kuliah penulisan iklan dalam program Pendidikan Bahasa Indonesia sebagian besar masih berpusat pada pengajar, sehingga membatasi kesempatan mahasiswa untuk terlibat dalam pembelajaran digital yang otentik. Penelitian ini bertujuan untuk menguji keefektifan Project-Based Digital Storytelling (PBDS) dalam meningkatkan keterampilan penulisan iklan mahasiswa. Sebuah studi kuasi-eksperimental dengan desain kelompok kontrol tidak setara dilakukan terhadap 45 mahasiswa sarjana, yang terdiri dari kelompok eksperimen (n = 23) dan kelompok kontrol (n = 22). Data dikumpulkan melalui tes prestasi penulisan iklan pra-tes dan pasca-tes, kemudian dianalisis menggunakan statistik deskriptif, uji-t sampel independen dan berpasangan, normalized gain (N-Gain), serta Cohen's d. Hasil penelitian menunjukkan bahwa kelompok eksperimen secara signifikan mengungguli kelompok kontrol dalam prestasi pascatest (p < 0,001), memperoleh N-Gain yang lebih tinggi (0,71), dan menunjukkan ukuran efek yang besar (d = 1,61). Para mahasiswa juga menunjukkan peningkatan yang signifikan dalam integrasi multimedia, kreativitas, kualitas pesan persuasif, dan kinerja presentasi. Temuan-temuan ini menunjukkan bahwa PBDS merupakan pendekatan pedagogis yang efektif untuk mengintegrasikan penulisan persuasif, penceritaan digital, dan komunikasi multimodal sekaligus memperkuat literasi digital serta kompetensi komunikasi abad ke-21 para mahasiswa di perguruan tinggi.